2013
DOI: 10.1093/gji/ggt043
|View full text |Cite
|
Sign up to set email alerts
|

Depth sensitivity of seismic coda waves to velocity perturbations in an elastic heterogeneous medium

Abstract: Numerous monitoring applications make use of seismic coda waves to evaluate velocity changes in the Earth. This raises the question of the spatial sensitivity of coda wave-based measurements. Here, we investigate the depth sensitivity of coda waves to local velocity perturbations using 2-D numerical wavefield simulations. We calculate the impulse response at the surface before and after a slight perturbation of the velocity within a thin layer at depth is introduced. We perform a parametric analysis of the obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
202
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(211 citation statements)
references
References 45 publications
9
202
0
Order By: Relevance
“…We also expect that this coda window will minimize the contribution of scattered body waves. Obermann et al (2013a) showed with numerical experiments that the body wave contribution will be dominant after six times the normalized transport mean free time t* = l/c where l is the transport mean free path and c is the surface wave velocity. As mentioned in Obermann et al (2013a), the estimation of the transport mean free path is often difficult.…”
Section: Data and Analysismentioning
confidence: 93%
“…We also expect that this coda window will minimize the contribution of scattered body waves. Obermann et al (2013a) showed with numerical experiments that the body wave contribution will be dominant after six times the normalized transport mean free time t* = l/c where l is the transport mean free path and c is the surface wave velocity. As mentioned in Obermann et al (2013a), the estimation of the transport mean free path is often difficult.…”
Section: Data and Analysismentioning
confidence: 93%
“…A precise analysis of the depth where the velocity changes occur would require the correct identification of the wavefield properties. Based on the assumption that the seismic coda is dominated by surface waves (Obermann et al 2013), we can obtain a rough depth estimate of the volume influencing the measurements. As there is no local velocity model available for the surroundings of station PATCX, we use an idealized half-space model with p-wave velocity v p = 2000 ms −1 , s-wave velocity v s = 1000 ms −1 and density ρ = 2.5 g cm −3 .…”
Section: Transient Velocity Changesmentioning
confidence: 99%
“…In general the sensitivity of coda waves is a combination of surface wave and body wave sensitivities with gradual transition from surface to body waves with increasing lapse time (Obermann et al 2013). This transition is faster for stronger medium heterogeneity favouring the conversion between the wave types.…”
Section: Selection Of the Frequency Bandmentioning
confidence: 99%
“…In general, amplitudes of the velocity variations systematically decrease for time windows in later parts of the coda. Obermann et al (2013) showed that the depth sensitivity of coda waves can be related to a combination of bulk wave sensitivity and surface wave sensitivity. At early times in the coda, most of the waves propagate as surface waves at shallow depths, and are therefore sensitive to shallow changes.…”
Section: Velocity Changes For Different Station-pairs and Componentsmentioning
confidence: 99%
See 1 more Smart Citation